(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2025)
The article outlines the impact of the application of neuro-pedagogical knowledge in foreign language teaching on the pupils’ mastery of English as a foreign language, specifically on the level of their four communicative language skills. The indications of recent neurolinguistic research that foreign language teaching (FLT) must be based on enabling pupils to develop their linguistic abilities through participation in authentic, real life communication situations, or at least situations resembling real life in the classroom. (1) Using brain research methods play an important role to improve teaching foreign languages for people in the classroom. Therefore, this paper explores how to use brain to memory words and phrases in neurolinguistic field.